2006
DOI: 10.1111/j.1469-8749.2006.tb01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pitfalls in paediatric ischaemic stroke

Abstract: Diagnosing ischaemic stroke and determining its cause is difficult in children. Both are important for selection of treatment and prediction of outcome. This study explored the diagnostic changes that lead to a delay in the correct diagnosis of paediatric stroke. Case histories of 45 children with ischaemic stroke (31 males, 14 females; median age 6y; age range 2mo–16y) were retrospectively reviewed. The initial clinical diagnosis, based on the interpretation of presenting symptoms, was compared with the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…We have recently shown that in 42% of children with ischemic stroke, the initial symptoms were wrongly attributed to another neurological disorder than stroke. 14 Pediatricians and (pediatric) neurologists should be aware of the high likelihood of a nonabrupt onset of symptoms in children with AIS, which could certainly lead to a more rapid diagnosis of stroke. Although the safety of thrombolytic therapy in children has not been established and thrombolysis should therefore not yet be routinely applied in childhood AIS, both the nonacute onset of deficits, and the large delay until hospitalization severely hinder the potentially beneficial future application of thrombolysis in children with AIS.…”
Section: The Recognition Of Strokementioning
confidence: 99%
“…We have recently shown that in 42% of children with ischemic stroke, the initial symptoms were wrongly attributed to another neurological disorder than stroke. 14 Pediatricians and (pediatric) neurologists should be aware of the high likelihood of a nonabrupt onset of symptoms in children with AIS, which could certainly lead to a more rapid diagnosis of stroke. Although the safety of thrombolytic therapy in children has not been established and thrombolysis should therefore not yet be routinely applied in childhood AIS, both the nonacute onset of deficits, and the large delay until hospitalization severely hinder the potentially beneficial future application of thrombolysis in children with AIS.…”
Section: The Recognition Of Strokementioning
confidence: 99%
“…15 Symptoms are frequently attributed to other problems such as migraine, encephalitis, tumors and Todd's paralysis following seizures. 16 For this reason research into the use of imaging to target acute thrombolytic therapy at the retrievable penumbra may be required in line with recent multicentre adult studies. 17 Geographically located stroke units within tertiary paediatric centres are not feasible given the small numbers of patients presenting at any one time with stroke.…”
Section: Thrombolysis In Paediatric Strokementioning
confidence: 94%
“…1). Since risk factors for childhood stroke differ from those in adults and the presence of inherited thrombophilic conditions is much rarer in this peculiar clinical setting, the role of familial history might be helpful but not essential to guide the clinical decision making [95]. Although there is no evidence-based management, screening for thrombophilia should be hence be limited to a specific subset of previously healthy children, where the most common pathologies (infections, congenital or acquired heart disease) cannot be identified [8].…”
Section: Considerations On Thrombophilia Screening For Arterial Ischementioning
confidence: 98%